Sistem Absensi Apel Pagi Dosen dan Staf STIKES Hang Tuah Surabaya Berbasis Web - Agustinus Setiono (Jurnal Publikasi Teknik Informatika, 2026)
Morning roll call is an important routine activity to improve discipline and cooperation on campus. Attendance recording during morning roll call, which is currently carried out manually by officers, has the potential to cause errors and requires time for recapitulation. This study aims to design and develop a web-based morning roll call attendance system for lecturers and staff at STIKES Hang Tuah, with a focus on simplifying the attendance recording process, speeding up reporting, and improving the accuracy of morning roll call attendance data. This system is built using web-based technology that allows officers to take attendance digitally, easily and quickly during morning roll call. This research is R&D research with a development process that refers to the AGILE method development stages. The development stages include the plan, design, develop, testing, deploy, review, and launch stages. The results of the study show that this system is capable of automating morning roll call attendance recording, providing attendance reports that can be accessed in real-time, and minimizing the potential for data errors or manipulation. With this web-based attendance system, it is hoped that the morning roll call attendance process will become more efficient, transparent, and can improve discipline among lecturers and staff at STIKES Hang Tuah Surabaya.